Gram-positive heme acquisition - Shipelskiy, Yan (Kansas State University, 2017)
Gram-positive bacteria are characterized by a single lipid bilayer with a thick peptidoglycan layer. This group of organisms contains bacteria commonly associated with human infection, including: Staphylococcus aureus, Listeria monocytogenes, Bacillus anthracis and Streptococcus pneumoniae among others. These bacteria have a common system for importing iron in the form of heme, which is acquired by proteins containing heme-binding NEAT (NEAr iron Transporter) domains. The heme acquisition system in S. aureus is termed the Iron Surface Determinant (Isd) system and in L. monocytogenes is termed Heme Binding Protein (Hbp) and Heme/Hemoglobin Uptake Protein (Hup). These proteins work together to obtain heme from hemoglobin and then transport the heme into the cytoplasm via well characterized ABC-transporters. Although there have been clinical trials with antibodies directed against Isd proteins, there are currently no antibiotics targeting iron uptake systems in bacteria in general. Building upon fluorescent approaches for detection of iron uptake in Gram negative organisms, this work develops fluorescent heme acquisition detection in Gram positive organisms. The spectrofluorimetric methodology facilitates the understanding of heme acquisition protein interactions and mechanisms in bacteria. This work could subsequently be used to identify inhibitors of Gram positive bacterial iron uptake systems, and develop a new target for antibiotic action.
Keywords: Iron; Heme; Antibiotics; Infectious Diseases; NEAT-domain; TonB